Management of idiopathic pulmonary fibrosis: selected case reports - Michael Kreuter; Peter Kardos; Victor Hoffstein (European Respiratory Review, 2014)
In 2011, revised international guidelines were issued jointly by the American Thoracic Society, the European Respiratory Society, the Japanese Respiratory Society and the Latin American Thoracic Association, which provide a valuable framework for the diagnosis and management of idiopathic pulmonary fibrosis (IPF). However, due to the complexity of IPF, these guidelines may not comprehensively account for the management of individual IPF patients in clinical practice. We describe three patient cases that were presented and discussed during the 2013 AIR: Advancing IPF Research meeting in Nice, France. These cases highlight the heterogeneity in the presentation, history and clinical course of IPF, together with expert insights regarding the diagnosis and management of IPF in the real-life setting.